Strategies for Preventing and Treating Oral Mucosal Infections Associated with Removable Dentures: A Scoping Review - Adriana Barbosa Ribeiro; Pillar Gonçalves Pizziolo; Lorena Mosconi Clemente; Helena Cristina Aguiar; Beatriz de Camargo Poker; Arthur Augusto Martins e Silva; Laís Ranieri Makrakis; Marco Aurelio Fifolato; Giulia Cristina Souza; Viviane de Cássia Oliveira; Evandro Watanabe; Cláudia Helena Lovato da Silva (MDPI AG, 2024)
Oral infections occur due to contact between biofilm rich in Candida albicans formed on the inner surface of complete dentures and the mucosa. This study investigated historical advances in the prevention and treatment of oral mucosal infection and identified gaps in the literature. Bibliographic research was conducted, looking at PubMed, Embase, Web of Science, and Scopus, where 935 articles were found. After removing duplicates and excluding articles by reading the title and abstract, 131 articles were selected for full reading and 104 articles were included. Another 38 articles were added from the gray literature. This review followed the PRISMA-ScR guidelines. The historical period described ranges from 1969 to 2023, in which, during the 21st century, in vitro and in vivo studies became more common and, from 2010 to 2023, the number of randomized controlled trials increased. Among the various approaches tested are the incorporation of antimicrobial products into prosthetic materials, the improvement of oral and denture hygiene protocols, the development of synthetic and natural products for the chemical control of microorganisms, and intervention with local or systemic antimicrobial agents. Studies report good results with brushing combined with sodium hypochlorite, and new disinfectant solutions and products incorporated into prosthetic materials are promising.